Pilgrimage Site Beyond Politics: Experience of the Sacred and Interreligious Dialogue in Olovo (Bosnia) - Belaj, Marijana (Array, 2012)
In Bosnia and Herzegovina conflicting social memories and interpretations of the past and presence of the three ethnic (and religious) entities, as well as the country’s structure as defined by the Dayton Agreement (1995), make interreligious (and interethnic) dialogue hard to accomplish. Interreligious dialogue among high representatives of various religious communities and theologians, the "top-down dialogue", is enhanced by the Interreligious Council of Bosnia and Herzegovina and carried out as a peacebuilding project. The "top-down dialogue" stands in juxtaposition to the dialogue of the believers, "the bottom-up dialogue". The latter takes place in spontaneous ways, based on friendly contacts and encounters through religious experience. Ecumenism expressed in the beliefs of the former group is more political, while within the latter group religious dimension is more stressed (Silajdžić). This paper focuses on the point of view of believers and analyzes interreligious "bottom-up dialogue" in Olovo in Bosnia, a pilgrimage (Catholic) shrine shared by Muslims and Catholics. In Bosnia and Herzegovina conflicting social memories and interpretations of the past and presence of the three ethnic (and religious) entities, as well as the country’s structure as defined by the Dayton Agreement (1995), make interreligious (and interethnic) dialogue hard to accomplish. Interreligious dialogue among high representatives of various religious communities and theologians, the "top-down dialogue", is enhanced by the Interreligious Council of Bosnia and Herzegovina and carried out as a peacebuilding project. The "top-down dialogue" stands in juxtaposition to the dialogue of the believers, "the bottom-up dialogue". The latter takes place in spontaneous ways, based on friendly contacts and encounters through religious experience. Ecumenism expressed in the beliefs of the former group is more political, while within the latter group religious dimension is more stressed (Silajdžić). This paper analyzes interreligious "bottom-up dialogue" in Olovo in Bosnia, a pilgrimage (Catholic) shrine shared by Muslims and Catholics. The emphasis is placed on the dialogue of religious experience, that is, on ways in which the Sacred is experienced and perceived. The paper deals with the dialogue of life (the way living space is shared) and the dialogue through actions (people’s solidarity in extraordinary and everyday conditions). The dialogue of religious experience is highlighted due to the fact that a shared experience of the Sacred within the shrine is stressed both in historical testimonies and in the contemporary interaction of the two religions in Olovo. The same goes for the sharing of pilgrimage time and space, as well as the common set of narratives linked to the Sacred and experiences of the Sacred.